2009
DOI: 10.1200/jco.2008.17.2254
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ER-α36, a Novel Variant of Estrogen Receptor α, and Resistance to Tamoxifen Treatment in Breast Cancer

Abstract: PURPOSE Recently, a 36-kDa variant of estrogen receptor alpha (ER-alpha66), ER-alpha36, has been identified and cloned. ER-alpha36 predominantly localizes on the plasma membrane and in the cytoplasm and mediates a membrane-initiated "nongenomic" signaling pathway. Here, we investigate the association between ER-alpha36 expression and tamoxifen resistance in patients with breast cancer. PATIENTS AND METHODS ER-alpha36 protein expression in tumors from 896 women (two independent cohorts, 1 and 2) with operable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
127
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(136 citation statements)
references
References 27 publications
7
127
0
2
Order By: Relevance
“…The activity of the NFκB signaling cascade is associated with mammary carcinogenesis, especially tumors with an aggressive and ERnegative phenotype [9]. ER-α36 expression is regulated differently from ER-α66, consistent with the findings that ER-α36 is expressed in specimens from ER-negative breast cancer patients and established ER-negative breast cancer cells that lack ER-α66 expression [10,11]. Although the function of ER-α36 has been studied in cancer, to our knowledge, it has not yet been known in the nervous system.…”
Section: Introductionsupporting
confidence: 74%
“…The activity of the NFκB signaling cascade is associated with mammary carcinogenesis, especially tumors with an aggressive and ERnegative phenotype [9]. ER-α36 expression is regulated differently from ER-α66, consistent with the findings that ER-α36 is expressed in specimens from ER-negative breast cancer patients and established ER-negative breast cancer cells that lack ER-α66 expression [10,11]. Although the function of ER-α36 has been studied in cancer, to our knowledge, it has not yet been known in the nervous system.…”
Section: Introductionsupporting
confidence: 74%
“…Approximately 70% of breast cancer cases are ERα-positive, and the remaining 30% are ER-negative [10]. ERα-36 is a variant of conventional ERα, which lacks both transcriptional activation domains of ERα-66, retains DNA-binding domain, partial dimerization and ligand-binding domains, and possesses a unique 27 amino acid domain that replaces the last 138 amino acid of ERα-66 [11,13]. It was found that ERα-36 expression levels were higher in ERnegative tumors and lower in ER-positive tumors [12].…”
Section: Discussionmentioning
confidence: 99%
“…ERα-36 was expressed in ER-negative tumor samples and ER-negative breast cancer cell lines [14]. Some studies have suggested that ERα-36 is involved in nongenomic estrogen signaling, and ERα-36 promotes cell proliferation via the MAPK/ERK pathway in ER-negative breast cancers [13,14]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, expression of the variant ER-α36 affects estrogen signaling and is associated with tamoxifen resistance in breast cancer [45] . In addition, the localization of ER variants in breast cancer cells reportedly differs from that of wild type ER [42,46] .…”
Section: The Role Of Er Variants In Cancer Cellsmentioning
confidence: 99%